Comparative analysis between optimum configurations of finned tube heat exchanger: Application for solar drying. (December 2020) - Chaanaoui, Meriem; Ettahi, Khadija; Abderafi, Souad; Vaudreuil, Sébastien; Bounahmidi, Tijani
Abstract: A comparative study is made between various optimized configurations of finned tube heat exchanger used to transfer thermal energy from a solar parabolic trough collector to a bench-scale dryer. The exchanger design relies on the logarithmic mean temperature difference (LMTD) and conjugate directions optimization method already integrated into the Engineering Equation Solver software (EES). Total cost minimization was set as the objective function. The model is first tested with previous literature results before being used to compare optimum configurations of four distinct heat exchanger configurations. The effect of five geometric and operating parameters is investigated. Results show that the third heat exchanger configuration (HX3 ) yields the lowest costs. Therminol -LT and -VP1, as well as Dowtherm -Q and -A, were found as the best working fluids for this application. Using copper as both tubes and fins material results in the smallest heat transfer surface area because of its high thermal conductivity. When economics are considered, aluminum and stainless steel alloys become suitable alternatives for fins and tubes, respectively. This yields savings of more than 40% on total costs from an all-copper construction.